Clinical outcome after total neoadjuvant treatment (CAO/ARO/AIO-12) versus intensified neoadjuvant and adjuvant treatment (CAO/ARO/AIO-04) a comparison between two multicenter randomized phase II/III trials - Diefenhardt, Markus; Fleischmann, Maximilian; Martin, Daniel; Hofheinz, Ralf-Dieter; Piso, Pompiliu; Germer, Christoph-Thomas; Hambsch, Peter; Grützmann, Robert; Kirste, Simon; Schlenska-Lange, Anke; Ghadimi, Michael; Rödel, Claus; et al. (Radiotherapy and oncology, 2023)
Background - Total neoadjuvant therapy (TNT) can enhance local tumor regression, but its survival benefits compared to intensified chemoradiotherapy (CRT) followed by adjuvant chemotherapy (CT) remain unclear. - Methods - This is a secondary comparison between 607 patients treated with intensified 5-FU/Oxaliplatin neoadjuvant CRT and adjuvant CT within the experimental arm of the CAO/ARO/AIO-04 phase III trial, and 306 patients treated with TNT within the CAO/ARO/AIO-12 phase II trial. Comparison between clinical-pathological characteristics, surgical quality, and post-surgical complications were analyzed using the Pearson’s Chi-squared or Mann-Whitney U test. Oncological outcome was examined with log-rank, Gray’s test, and multivariate cox regression. In addition, further subgroup analyses and propensity score matching were performed to optimize the balance of baseline covariates. - Findings - Patients treated with CRT followed by consolidation CT had a significantly higher rate of pathological complete remission (pCR) compared to patients treated within the experimental arm of the CAO/ARO/AIO-04 trial (25.3 % vs 17.3 %, P = 0.04). Post-surgical complications were less common in the CAO/ARO/AIO-12 trial. After a median follow-up of 46 months, clinical outcome did not differ significantly in the overall cohort, in any subgroup or after propensity score matching. In multivariate analysis, disease-free survival (DFS) was similar between the experimental arm of the CAO/ARO/AIO-04 trial and treatments arms of the CAO/ARO/AIO-12 trial (vs arm A: HR 0.92 [95 % CI 0.62-1.37], P = 0.69; vs arm B: HR 1.06 [95 % CI 0.72-1.58], P = 0.76). - Interpretation - Notwithstanding the limitations of intertrial comparison, TNT did not improve long term oncological outcome in our study compared to the intensified neoadjuvant CRT and adjuvant CT treatment in the CAO/ARO/AIO-04 trial. Improved response rates after TNT offers an attractive option to explore organ preservation in selective patients with locally advanced rectal cancer.
Online verfügbar: 23. Dezember 2022, Artikelversion: 4. Januar 2023
Gesehen am 01.08.2024